Effect of 12 weeks of detraining and retraining on the cardiorespiratory fitness in a competitive master athlete: a case study - Lepers, Romuald; Mater, Adrien; Assadi, Hervé; Zanou, Nadège; Gremeaux, Vincent; Place, Nicolas (Frontiers in Physiology, 2024)
PurposeThis study examined the physiological effects of 12 weeks of detraining and retraining in a highly trained master triathlete (age 53.8 years).MethodsVariables associated with swimming, cycling, and running performance, including V˙O2max, peak power output (PPO), gross cycling efficiency (CE), running maximal aerobic velocity (MAV), running economy (RE), muscle strength, and body composition were assessed before the last race of the season (baseline), after 12 weeks of detraining, and after 12 weeks of retraining.ResultsDetraining resulted in a 9.1% and 10.9% decrease in relative V˙O2max for cycling and running, respectively. PPO and MAV declined by 12.7% and 8.6%, respectively. After detraining, CE decreased by 6.2%, and RE was 22% higher than the baseline. The maximal strength capacity of the knee extensor muscles decreased by an average of 8.2%. Body fat percentage increased from 10.5% to 13.8%, while lean mass decreased by 2.2 kg. After retraining, almost all variables returned to baseline or even slightly increased, except RE and lean mass, which did not return to baseline.ConclusionAfter 12 weeks of detraining, a lifelong master triathlete can regain his cardiorespiratory fitness (i.e., V˙O2max) with 12 weeks of progressive and structured retraining, but his running economy and lean mass remain slightly depressed.